Modification of togok (tidal trap) for reducing bycatch by using BRD vent - Nofrizal Nofrizal; Muhamad Mauliddin; Romie Jhonnerie (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
One effort to reduce bycatch in togok is to modify the togok by creating a vent to reduce bycatch by BRD. The BRD installed on the togok was a rope BRD vent made of Polyethelene (PE) with a diameter of 2 mm. The rope BRD vent is attached to the top of the cod-end as an escape vent 25 x 50 cm. The escape vent and the stash cod-end are covered with a net with a mesh size of 5 mm. The cover net aims to collect data on fish catches that pass through the rope BRD vent. The percentage of fish that pass through the rope BRD vent can be calculated, and measure the size of the fish caught in the cod-end and covered as an indicator of the effectiveness of the rope BRD vent on togok. This experiment was carried out for 20 days of fishing operation and 40 hauls. The results showed that the catch of togok without rope BRD vent (conventional) and togok with modified rope BRD vent were different (p 0.05), where the catch of conventional togok was 468.34 kg, and the catch of modified togok was 305.235 kg. The fishing catches in the cod end and cover sections the most are bycatch with 51% and 54% of the percentage of the total catch, and the least in the cod end is the discarded catch, which is 21% of the percentage of the total catch and on the cover is the main catch (main catch) with 19% of the percentage of the total catch.The average size of the catch of togok species of fish is there are many immature sizes, and the average size of the catch of togok species of shrimp is there are in maturity size.Keywords:BycatchBycatch excluder device (BRD)DiscardMain catch